Who Speaks for Nahdlatul Ulama? - Rahman, Jasmine Hasna Nafila (PCD Journal, 2024)
In Indonesia’s presidential elections, the act of claiming to represent Nahdlatul Ulama (NU) has emerged as a potent political strategy—one pursued not only by political parties but also by religious elites, polling institutions, and self-proclaimed “neutral” actors. This article investigates how such claims are constructed and contested within the digital public sphere in the lead-up to the 2024 presidential election. Drawing on Saward’s theory of representative claims, it analyses 413 online news articles using a combination of Discourse Network Analysis and qualitative text analysis. Empirically, the study maps who is speaking, about what, and on whose behalf—offering analytical insight into how legitimacy is narrated and performed. Theoretically, it extends the application of representative claims theory by demonstrating how legitimacy is negotiated in contexts where the constituency is internally fragmented, pluralistic, and contested—rather than unified or binary. These findings highlight the fluid nature of representation, especially in socio-religious communities such as NU, where claims to representation are constantly produced, challenged, and reframed in public discourse.